A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan - Nozaki, Takao; Shimura, Noriyoshi (Zootaxa, 2020)
A new species of the genus Goera, G. rupicola, is described based on adult and immature stages from Amami-Oshima, southwestern Japan. The larvae of this species inhabit wet cliff faces where water trickles over the surface. This is the first madicolous species reported in the genus Goera.